Influence of Economic Recession on Undergraduate Students Academic Performance in Kwara State: Recession, Gender, Performance, Global Economy - Amos Ochayi Onojah; Gboyega Ayodeji Aladesusi; Adekola Musiliu Aderoju (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2021)
This study was carried out to investigate the influence of economic recession on undergraduate students’ Academic Performance in Kwara-state. The research was a descriptive type using the survey method. The study sample was drawn from three (3) Universities in kwara state, Nigeria. 380 respondents were sampled, but 246 of the 380 questionnaires were properly filled and returned. The respondents were 246 students, 132 were males and 114 females. A structured questionnaire was utilized in collecting data while mean was used to analyze the data collected. The results of the study indicated that economic recession has negative influence on global economy. Also, recession has negative effect on undergraduates’ students’ academic performance. There was no significant difference in the effect of economic recession on students’ academic performance based on gender. No significant difference existed in the effect of economic recession on students’ academic performance based on parent’ status.